Elaborasi Komunikasi Krisis Polri: Analisis Penanganan Kasus Penembakan Brigadir J Menggunakan Situational Crisis Communication Theory - Desmalinda Makdin; Harya Rifky Pratama; Deska Damayanti; Adin Noviana (IPTEK-KOM : Jurnal Ilmu Pengetahuan dan Teknologi Komunikasi, 2023)
This study aims to elaborate crisis response strategy carried out by the National Police Public Relations Division in handling the shooting case of Brigadier J. Motivated by the crisis faced by the National Police as a result of the death of Brigadier J at the official house of the Head of the National Police Propam Division. The President requested that the Police be transparent and thoroughly investigate the case. The study was conducted using mixed research methods, namely quantitative content analysis on Instagram content @divisihumaspolri and qualitative descriptive analysis by looking at previous research related to crisis communication strategies. Researchers also grabbed data focusing on some keywords of the Brigadier J shooting case across social media using a media monitoring service based on the Intelligence Socio Analytics system in the period July 8 to August 30 2022, to review public sentiment and see the spread of issues. These research findings point to content patterns @divisihumaspolri, public sentiment, and reputation strategies. The results concluded that the National Police Public Relations Division had not implemented crisis communication protocols properly and could not minimize bad assumptions from the public.